THE ROLE OF CLASSROOM TEACHERS IN IMPLEMENTING GUIDANCE AND COUNSELING SERVICES TO ADDRESS STUDENTS’ ACADEMIC AND SOCIAL PROBLEMS: A QUALITATIVE STUDY - Suastini, Ni Wayan; Juliawan, I Wayan; Mulyawan, I Nyoman Rajeg; Susanta, I Wayan (Jurnal Ilmiah Pendidikan Citra Bakti, 2026)
This study aims to determine the alignment between the role of classroom teachers as implementers of guidance and counseling services and the official guidelines for guidance and counseling services at SD N 3 Banjar Anyar. This research is a field study using a descriptive qualitative approach. Data were collected through observation, interviews, and documentation. The data analysis technique employed is the interactive model of Miles and Huberman, which includes data reduction, data display, and conclusion drawing. The subject of this research is the classroom teachers at SD N 3 Banjar Anyar. The results of the study indicate that the problems experienced by students vary across grade levels. In Grade I, students show a low ability to adjust to a new social environment. In Grade III, students experience difficulties in reading and writing, feel bored during learning, and exhibit disruptive behavior and a tendency to engage in fights in the classroom. In Grade VI, the problems include truancy, low learning motivation, and anxiety about facing the National Final Examination (UAN). The role of classroom teachers as implementers of guidance and counseling has not been carried out optimally in accordance with the established guidelines. This is due to limited knowledge of guidance and counseling implementation, the absence of specific training for teachers, and the lack of a well-planned and systematic guidance and counseling program developed by the school.